Zirconia Implants in Esthetic Areas: 4-Year Follow-Up Evaluation Study - Andrea Enrico Borgonovo; Rachele Censi; Virna Vavassori; Oscar Arnaboldi; Carlo Maiorana; Dino Re (Hindawi Limited, 2015)
Objectives. The aim is to evaluate the survival and success rates, as well as the marginal bone loss (MBL) and periodontal indexes of zirconia implants positioned in the esthetic jaw areas. Materials and Method. 13 patients were selected and 20 one-piece zirconia implants were used for the rehabilitation of single tooth or partially edentulous ridge in the esthetic jaw areas. Six months after surgery and then once a year, a clinical-radiographic evaluation was performed in order to estimate peri-implant tissue health and marginal bone loss. Results. The survival and success rates were 100%. The average marginal bone loss from baseline to 48 months after surgery was +2.1 mm. Four years after surgery, the median and the mode for visible Plaque Index and Bleeding On Probing resulted 1 whereas Probing Pocket Depth amounted to 3 mm (SD = ±0.49 mm). Conclusion. One-piece zirconia dental implants are characterized by high biocompatibility, low plaque adhesion, and absence of microgap that can be related to the clinical success of these implants even in the esthetic areas.